1993
DOI: 10.1039/jm9930300903
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for the formation of a passivating layer during chemomechanical polishing of silica by a hydrogen difluoride-based reagent

Abstract: The sparingly soluble material (the passivating layer) formed during chemomechanical polishing of silica wafers by [HF,J--cerium(~v) oxide-sucrose mixtures at low pH has been identified as K,SiF, coated with a thin silica layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…A passivating layer of K 2 SiF 6 has been observed during chemomechanical polishing of silica in the presence of KHF 2 . Boyle et al report an IR spectrum in which the main bands of the thin-film spectrum agree with the bulk spectrum of Badachhape et al In an investigation of the effects of alkali metal and quaternary-ammonium cations on the rate of anodic formation of por-Si, white, sparingly soluble films formed on the external surface in the presence of K + , Rb + , and Cs + . These were identified as hexafluorosilicates. , Stain etching of silicon in HF−oxidant−H 2 O (oxidant = K 2 Cr 2 O 7 , KBrO 3 , or KMnO 4 ) has been studied. , As the concentration of the oxidant is increased, the etch rate increases to a limiting value as the thickness of the K 2 SiF 6 increases.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…A passivating layer of K 2 SiF 6 has been observed during chemomechanical polishing of silica in the presence of KHF 2 . Boyle et al report an IR spectrum in which the main bands of the thin-film spectrum agree with the bulk spectrum of Badachhape et al In an investigation of the effects of alkali metal and quaternary-ammonium cations on the rate of anodic formation of por-Si, white, sparingly soluble films formed on the external surface in the presence of K + , Rb + , and Cs + . These were identified as hexafluorosilicates. , Stain etching of silicon in HF−oxidant−H 2 O (oxidant = K 2 Cr 2 O 7 , KBrO 3 , or KMnO 4 ) has been studied. , As the concentration of the oxidant is increased, the etch rate increases to a limiting value as the thickness of the K 2 SiF 6 increases.…”
Section: Introductionmentioning
confidence: 60%
“…A passivating layer of K 2 SiF 6 has been observed during chemomechanical polishing of silica in the presence of KHF 2 . Boyle et al 31 report an IR spectrum in which the main bands of the thin-film spectrum agree with the bulk spectrum of Badachhape et al 32 In an investigation of the effects of alkali metal and quaternary-ammonium cations on the rate of anodic formation of por-Si, white, sparingly soluble films formed on the external surface in the presence of K + , Rb + , and Cs + . These were identified as hexafluorosilicates.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…K 2 SiF 6 crystallite, spontaneously generating when the solubility product of K 2 SiF 6 exceeded to 6.3 × 10 −7 mol 3 dm −9 , is a byproduct during the forming process of porous silicon [ 11 ]. Hadjersi et al reported that an insoluble solid-phase film (K 2 SiF 6 ) covered the top of porous silicon layer by the etching of silicon-coated silver film in HF-oxidizing solution [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, K 2 SiF 6 crystallites have been observed during the different wetting etchings of silicon substrate in the presence of HF and K + ions, such as chemomechanical polishing [ 11 ], stain etching [ 12 ], laser-assisted etching [ 13 ], and metal-assisted electroless etching (MAEE) [ 14 , 15 ]. These K 2 SiF 6 crystallites are insoluble in dilute HF solution and to some extent can prevent the etchant solution from the contact with silicon surface.…”
Section: Introductionmentioning
confidence: 99%